In vitro study sargassum sp. effervescent towards antifungal and compressive strength silicone based softliner - Kusumawardani, Chaterina Diyah Nanik; Teguh, Paulus Budi; Lestari, I Gusti Made Oka; Ashrin, Meinar Nur; Maharani, Aulia Dwi; Razak, Arifzan; Ariestania, Vivin; Budiman, Widaningsih; Artha, Rizko Wira; Apsari, Anindita (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Softliner is commonly used to provide convenience for edentulous patients. However, the use of softliner can cause denture stomatitis due to colonization of Candida albicans. Sargassum sp. contains active compounds of steroids, alkaloids, phenols, triterpenoids, act as antibacterial and antifungal. The use of Sargassum sp. in the form of effervescent as a denture cleanser can prevent denture stomatitis, and it’s expected not to affect the compressive strength. This study aimed to study the concentration variation of Sargassum sp. effervescent towards antifungal and compressive strength silicone based softlinerMethod: 20 sampels of silicone based softliner (10x3x2mm) divided into 5 groups. K(-) soaked in sterilled aquadest; K(+) in Polident solution; P1 in 10% effervescent Sargassum sp. solution; P2 20% ; P3 40%, for 15minutes. Candida calculated by colony counter (CFU/ml). Compressive strength measured by Universal Testing Machine.Result: Candida albicans in the K+ group is the lowest, while the K- group shows the highest value. In P1, P2, P3 group the value of Candida albicans is higher than K+ group, but much lower than K-. The compressive strength of K+ group shows the lowest value but in P3 group shows the highest value compared to other groups.Conclusion: The 10% concentration of effervescent extract Sargassum sp. is effective in reducing the number of Candida albicans in silicone based softliner compared to the K- group. The most effective concentration of effervescent extract Sargassum sp. in reducing the Candida albicans’ growth is 40%. The higher concentration of Sargassum sp. resulting in higher compressive strength.